2009
DOI: 10.1016/j.paid.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

A psychobiographical analysis of Brian Douglas Wilson: Creativity, drugs, and models of schizophrenic and affective disorders

Abstract: The suggestion of a relationship between creativity and mental disorder has existed for centuries, and has been advocated by many psychological researchers. The present analysis offers a consideration of the nature of mental disorder present in Brian Wilson, an individual recognised as one of the most creative figures in 20th century popular music. Using converging biographical evidence, and the diagnostic program Opcrit, Wilson's diagnosis is concluded to be schizoaffective. Employing details of his drug abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
0
17
0
1
Order By: Relevance
“…Not only does the artistic environment support substance use (see Table 1), but substances may, through mood effects, perform an important creativity-enhancing function. Alcohol has been noted as a self-medication for performance anxiety (Fehm & Schmidt, 2006), and cannabis and LSD are commonly used for creative intent (Belli, 2009; Fachner, 2006). In terms of psychosocial treatments, comorbid substance use problems may require separate attention using specialized strategies (Albanese & Pies, 2004; Vornik & Brown, 2006), which go beyond simple combination of the content specific to the two conditions (Conrod & Stewart, 2005; Quello, Brady, & Sonne, 2005).…”
Section: Performance Lifestyle As a Precipitating Or Perpetuating mentioning
confidence: 99%
See 1 more Smart Citation
“…Not only does the artistic environment support substance use (see Table 1), but substances may, through mood effects, perform an important creativity-enhancing function. Alcohol has been noted as a self-medication for performance anxiety (Fehm & Schmidt, 2006), and cannabis and LSD are commonly used for creative intent (Belli, 2009; Fachner, 2006). In terms of psychosocial treatments, comorbid substance use problems may require separate attention using specialized strategies (Albanese & Pies, 2004; Vornik & Brown, 2006), which go beyond simple combination of the content specific to the two conditions (Conrod & Stewart, 2005; Quello, Brady, & Sonne, 2005).…”
Section: Performance Lifestyle As a Precipitating Or Perpetuating mentioning
confidence: 99%
“…Circadian rhythm instability plays a causal role in BD (Murray & Harvey, in press) and this vulnerability is moderated by social rhythms (Malkoff-Schwartz et al, 1998; Malkoff-Schwartz et al, 2000). Creative occupations are characterized by abnormal 24 hour activity patterns: Working hours are typically at night, with rehearsals and other engagements scheduled during the day (Belli, 2009). Exacerbating this instability is work-related travel, including travel across time zones, a known risk for BD relapse (Katz, Knobler, Laibel, Strauss, & Durst, 2002).…”
Section: Performance Lifestyle As a Precipitating Or Perpetuating mentioning
confidence: 99%
“…Furthermore, Jones' (2007) findings showed that LSD changed a cartoon illustrator's style. Similarly, in Belli's (2009) case study, the modification of musical style was reported connected to substance use.…”
Section: Discussionmentioning
confidence: 82%
“…Belli (2009) Cannabis and LSD were unambiguously reported to influence Wilson's creativity. He smoked cannabis because of its auditory alteration.…”
Section: Various Substancesmentioning
confidence: 95%
“…Ayrıca yaratıcı uygulamalar çalışanların da motivasyonunu olumlu etkilemektedir. [33,[39][40][41][42][43][44] Hemşireliğin profesyonel bir meslek olarak kabulü ve diğer meslek gruplarından ayrımı için kuramları denemeleri, eleştirmeleri ve geliştirmeleri beklenmektedir. [45] Nitekim günümüzde ruh sağlığı ve hastalıkları hemşirelerinin ilgi alanlarında kuram geliştirme, kuramları birbirleriyle birleş-tirme bulunmaktadır.…”
Section: Ruh Sağlığı Ve Hastalıkları Hemşireliğinde Yaratıcılıkunclassified